Notes on the Dianous bimaculatus complex with description of a new species from China (Coleoptera, Staphylinidae) - Tang, Liang; Huang, Meng-Chi (Zootaxa, 2018)
A new species of the Dianous bimaculatus complex from China is described: D. hubeiensis Tang & Huang, sp. n. from Hubei Province. New distributional records are reported for Dianous flavoculatus Puthz, 1997 and D. hainanensis Puthz, 1997. A key to Chinese species of the Dianous bimaculatus complex is provided